Influence of knowledge sources on climate change awareness and adaptation priorities in Central Nepal - Lalit Pathak; Kamana Joshi (Discover Environment)
Abstract Climate change perceptions are shaped by the interplay between formal knowledge—acquired through formal education and mass media—and lived experiences of direct environmental impacts. This study investigates how these complementary knowledge sources influence climate awareness, risk perception, and pro-environmental behavior among diverse socio-professional groups in Central Nepal. A mixed-methods survey of 300 respondents across three districts (Kathmandu, Sindhupalchowk, and Chitwan) reveals an epistemological divide: professionals emphasize global-scale risks (e.g., glacier melt) while farmers focus on immediate local impacts (e.g., crop failure, erratic rainfall). Regression analysis shows that internalized personal norms (β = 1.01, p < 0.001) are the strongest predictors of pro-environmental behavior, with formal education playing a statistically non-significant role (β = −0.007, p = 0.746). The findings highlight the need for integrated adaptation strategies that integrate global scientific insights with local experiential knowledge, recommending community-led action and the recognition of indigenous knowledge systems. This research informs climate communication and policy design in Global South contexts by advocating for a multi-knowledge framework to climate adaptation.